Cardiac Arrest and Cardiopulmonary Resuscitation Outcome Reports: Update of the Utstein Resuscitation Registry Templates for Out-of-Hospital Cardiac Arrest: A Statement for Healthcare Professionals From a Task Force of the International Liaison Committee on Resuscitation (American Heart Association, European Resuscitation Council, Australian and New Zealand Council on Resuscitation, Heart and Stroke Foundation of Canada, InterAmerican Heart Foundation, Resuscitation Council of Southern Africa, Resuscitation Council of Asia); and the American Heart Association Emergency Cardiovascular Care Committee and the Council on Cardiopulmonary, Critical Care, Perioperative and Resuscitation. (November 2015) - Perkins, Gavin D.; Jacobs, Ian G.; Nadkarni, Vinay M.; Berg, Robert A.; Bhanji, Farhan; Biarent, Dominique; Bossaert, Leo L.; Brett, Stephen J.; Chamberlain, Douglas; de Caen, Allan R.; Deakin, Charles D.; Finn, Judith C.; et al.
Abstract: Utstein-style guidelines contribute to improved public health internationally by providing a structured framework with which to compare emergency medical services systems. Advances in resuscitation science, new insights into important predictors of outcome from out-of-hospital cardiac arrest, and lessons learned from methodological research prompted this review and update of the 2004 Utstein guidelines. Representatives of the International Liaison Committee on Resuscitation developed an updated Utstein reporting framework iteratively by meeting face to face, by teleconference, and by Web survey during 2012 through 2014. Herein are recommendations for reporting out-of-hospital cardiac arrest. Data elements were grouped by system factors, dispatch/recognition, patient variables, resuscitation/postresuscitation processes, and outcomes. Elements were classified as core or supplemental using a modified Delphi process primarily based on respondents' assessment of the evidence-based importance of capturing those elements, tempered by the challenges to collect them. New or modified elements reflected consensus on the need to account for emergency medical services system factors, increasing availability of automated external defibrillators, data collection processes, epidemiology trends, increasing use of dispatcher-assisted cardiopulmonary resuscitation, emerging field treatments, postresuscitation care, prognostication tools, and trends in organ recovery. A standard reporting template is recommended to promote standardized reporting. This template facilitates reporting of the bystander-witnessed, shockable rhythm as a measure of emergency medical services system efficacy and all emergency medical services system-treated arrests as a measure of system effectiveness. Several additional important subgroups are identified that enable an estimate of the specific contribution of rhythm and bystander actions that are key determinants of outcome.